2007
DOI: 10.1080/10641950701204430
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Hypertension in the Postpartum Period with Intravenous Hydralazine or Labetalol: A Randomized Clinical Trial

Abstract: This randomized clinical trial shows that intravenous hydralazine and intravenous labetalol are effective and safe in the management of severe hypertension in the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 8 publications
2
24
0
7
Order By: Relevance
“…Postpartum, hydralazine, labetalol, nifedipine, and methyldopa are appropriate for treatment of severe hypertension and during breastfeeding [341,342]. Oral captopril is effective outside pregnancy [343] and is acceptable during breastfeeding (http://toxnet.nlm.nih.gov/).…”
Section: Antihypertensive Therapymentioning
confidence: 99%
“…Postpartum, hydralazine, labetalol, nifedipine, and methyldopa are appropriate for treatment of severe hypertension and during breastfeeding [341,342]. Oral captopril is effective outside pregnancy [343] and is acceptable during breastfeeding (http://toxnet.nlm.nih.gov/).…”
Section: Antihypertensive Therapymentioning
confidence: 99%
“…13 Delgado De Pasquale et al showed no statistically significant difference between hydralazine and labetalol groups in the frequency of adverse reactions. 7 Similar to present study, headache was more frequently observed in the hydralazine group compared to labetalol in the study by Nombur et al 8 Deka Nabanita et al also reported a greater frequency of headache with hydralazine compared to labetalol.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is different from the studies conducted by De Gracia et al, Tabasi et al, Nombur LI et al and Nabanita et al where no significant differences were observed in the fetal outcome in both the groups. 6,8,9,13 …”
Section: Discussionmentioning
confidence: 99%
“…La hidralazina, vasodilatador arterio-selectivo, disminuye resistencia vascular periférica, aumenta la frecuencia cardiaca y el gasto cardiaco con aumento del flujo coronario, renal, cerebral, asplácnico y útero placentario, de primera línea para crisis hipertensivas en el embarazo y postparto (33)(34)(35), efectos colaterales frecuentes tenemos la presencia de palpitaciones, taquicardia, enrojecimiento, hipotensión, náuseas, vómito, diarrea, artralgia anorexia, con respecto a la seguridad en la lactancia es catalogado como de riesgo muy bajo (nivel 0), su excreción por la leche es clínicamente no significativa (16), la academia de pediatría lo considera una medicación usualmente compatible con la lactancia (21).…”
Section: Otros Antihipertensivosunclassified
“…El manejo inicial incluye la reducción rápida de la presión, por medio de antihipertensivos endovenosos, buscando metas de presión sistólica entre 140 y 150 mmHg; y diastólicas entre 90 y 100mmHg, con el fin no afectar la autorregulación de la vasculatura cerebral normal (35). Dentro de los antihipertensivos endovenosos de primera línea tenemos; el labetalol e Hidralazina, ambos efectivos y seguros para la crisis en el puerperio (33,34). Un ensayo clínico aleatorizado los comparo para la crisis en el puerperio, encontrando no diferencias significativas con respecto al alcance del control de las cifras tensionales propuestas como meta, la hidralazina alcanzo la meta en un 83,3% y el labetalol en un 87,5 % (P> 0,05), con respecto a resultados maternos como eclampsia, oliguria, síndrome de HELLP, hipertensión severa persistente no se encontraron diferencias entre los dos antihipertensivos (P>0.05), de igual manera no presentaron diferencias estadísticas con respecto a efectos colaterales (P>0.05) (33).…”
Section: Escenarios Clínicos En La Hipertensión Pospartounclassified